2012
DOI: 10.5007/2175-8077.2012v14n34p103
|View full text |Cite
|
Sign up to set email alerts
|

Criação ou destruição de valor na perspectiva do EVA® no ranking das maiores empresas da Revista Exame

Abstract: Objetivou-se verificar o comportamento das maiores empresas brasileiras em vendas, com atuação nas regiões Norte/Nordeste, Centro-Oeste, Sudeste e Sul, listadas na revista Exame Melhores e Maiores, a partir da perspectiva de criação ou destruição de valor doEVA®. Analisaram-se 316 empresas com o auxílio da estatística descritiva e da Análise de Correspondência para verificar a associação entre as empresas que mais criam valor (EVA®) e as regiões brasileiras e os setores de atuação. Constatou-se que 217 empresa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
(6 reference statements)
0
2
0
1
Order By: Relevance
“…From this analysis with the geographic regions, it was evidenced that a high creation of value is associated with the Midwest region, that is, organizations in that location have higher EVA®. When comparing the ranking of the largest companies, established by Exame Magazine, with the ranking elaborated from the EVA® perspective, it was found that only 5 of the 316 companies analyzed remained in their positions (DE MENESES, 2012).…”
Section: Research Related To the Themes Of This Studymentioning
confidence: 99%
“…From this analysis with the geographic regions, it was evidenced that a high creation of value is associated with the Midwest region, that is, organizations in that location have higher EVA®. When comparing the ranking of the largest companies, established by Exame Magazine, with the ranking elaborated from the EVA® perspective, it was found that only 5 of the 316 companies analyzed remained in their positions (DE MENESES, 2012).…”
Section: Research Related To the Themes Of This Studymentioning
confidence: 99%
“…Also, in the study conducted by Hall [35], the average value of EVA® of the sample companies was negative, indicating that South African industrial companies, on average, for the period analyzed, have destroy value instead of create. In the study conducted by Meneses, Cunha, De Luca and Holanda [36], which compared the ranking of the largest sales companies, established by Exame Magazine in 2010, found that of the 316 companies in the sample, 217 created value for investors, while 99 destroyed value.…”
Section: Analysis Of Eva® Valuesmentioning
confidence: 99%
“…Complementarmente, Meneses et al (2012) afirmam que entre as medidas de criação de valor de uma empresa, destaca-se o Valor Econômico Agregado (EVA), o qual é considerado uma medida de desempenho que avalia a rentabilidade de um investimento diante de outros investimentos.…”
Section: Avaliação De Empresasunclassified